Micropropagation of Thalictrum dalzellii Hook. Through Rhizome Buds - Rai2, P.Sharanappa1*; V. Ravishankar (Journal of Phytology, 2011)
An efficient micropropagation protocol was developed for Thalictrum dalzellii an endemic, endangered plant by using rhizome buds as explants.Ã‚Â In vitro germinated rhizome buds were used for the induction of multiple shoots on MS medium supplemented with thidiazuron (TDZ), benzylaminopurine (BAP) and Kinetin (KN). The presence of TDZ promoted a higher rate of shoot multiplication than BAP and KN. The maximum number of shoot multiplication was observed in TDZ at a concentration 0.5 mg l-1.Ã‚Â Shoot elongation was obtained when the culture transferred to MS basal medium.Ã‚Â The maximum percentage of rooting was obtained in half strength MS medium with 0.5 mg l-1 IBA.Ã‚Â Plantlets were successfully acclimatized under green house condition.Ã‚Â The acclimatized plantlets were morphologically similar to wild plants.